Ionic liquid electrolyte of lithium bis(fluorosulfonyl)imide/N-methyl-N-propylpiperidinium bis(fluorosulfonyl)imide for Li/natural graphite cells: Effect of concentration of lithium salt on the physicochemical and electrochemical properties - Liu, Chengyong; Ma, Xiaodi; Xu, Fei; Zheng, Liping; Zhang, Heng; Feng, Wenfang; Huang, Xuejie; Armand, Michel; Nie, Jin; Chen, Hanlin; Zhou, Zhibin (Electrochimica acta, 2014)
•Ionic liquid electrolytes containing various concentrations of lithium bis(fluorosulfonyl) imide (LiFSI) are characterized.•Their electrochemical properties on electrodes highly depend on the concentration of LiFSI.•High Li-ion reversibility in graphite electrodes are obtained in the LiFSI concentrated electrolytes.•SEI films on graphite electrodes mainly comprise reductive products of bis(fluorosulfonyl) imide anions. Binary electrolytes, comprising of lithium bis(fluorosulfonyl) imide (LiFSI) and ionic liquids (ILs) of N-methyl-N-propylpiperidinium bis(fluorosulfonyl) imide (PI13FSI) with various concentrations of LiFSI (i.e., LiFSI/PI13FSI in 0.05:1, 0.1:1, 0.2:1, 0.5:1, 0.8:1 and 1:1, by mole) have been investigated as electrolyte for Li-ion cells, in terms of phase behavior, thermal stability, density, viscosity, ionic conductivity, lithium-ion transference number, and electrochemical behaviors on Al, Pt, Ni, and composite natural graphite electrodes, with particular attention to the effect of concentration of LiFSI in PI13FSI on these properties. The stability of Al in the high potential region (3.0–5.0V vs. Li/Li+) has been confirmed in these electrolytes using cyclic voltammetry, chronoamperometry and SEM morphology. The anodic stability of these electrolytes on Pt electrode has been little affected by addition of LiFSI. Li deposition/stripping on Ni electrode shows low columbic efficiencies (< 45%) in these electrolytes, due to the continuous reduction of FSI− anions and PI13+ cations. Reduction of FSI− anions for forming solid electrolyte interphase (SEI) films on the graphite is observed at ca. 2.0V (vs. Li/Li+), followed by intercalation of Li+ ions and IL cations into graphite in these electrolytes at the first cathodic scan in CV measurements. The performances of SEI films formed on the graphite highly depend on the concentration of LiFSI, and a stable Li-ion conducting SEI film can only be formed in the electrolyte containing a high concentration of LiFSI. Li/natural graphite cell using LiFSI-PI13FSI (1:1, by mole) as electrolyte displays high specific capacities (> 360 mAh g−1) and columbic efficiencies (> 99%) after conditioning, except for a large irreversible capacity (139 mAh g−1) observed at the first cycle. Analyses of XPS and electrochemical impedance spectra reveal that a stable Li-ion conducting SEI film, mainly comprising reduction products of FSI− anions (e.g., LiF, LiOH, Li2SO3, and species containing NSO2-, FSO2-, and N−), has been formed on the graphite.